Research on the wear and miscrostructure of as crank shaft bearing coated with alloys of zn-10c and zn-20al-15c-5o - Hanbey Hazar; Omer Cihan (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2014)
The experiment of this study consists of coating the 6LD400 Lombardini crankshaft bearing surface with zinc based on two alloys using atmospheric plasma spray. The microstructure of the coatings and matrix have been investigated by the Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Compared to the matrix, the coated bearings have a more porous and homogeneous view. During the wearing test, the least mass loss occurred in the alloy Zn-25Cu-10Al-5O-15C, since the zinc-rich bearing surface has a lubricant function. With regard to the crankshaft, the optimum average micro hardness value is 51.5 HV which is seen in the Zn-10C alloy coated bearing